Evaluation of biogas production from swine manure using a UASB reactor (upflow anaerobic sludge blanket) with long-term operation (2024)
To meet Colombia’s energy needs by 2050, a total installed capacity of 42 MW across its power generation infrastructure is required. To achieve this, transitioning to cleaner energy sources, such as biomass—a non-conventional renewable energy—is necessary. Biomass is a promising renewable source for thermal and electrical energy production. This study researched the production of biogas from swine manure using a UASB reactor to valorize this waste. Swine manure was collected every 20 days from a pig farm with a capacity of 200 sows, located in Santa Rosa de Osos, Antioquia. The flow rate was increased three times (1.30 L d−1, 1.62 L d−1, and 2.08 L d−1) to reduce the hydraulic retention time (HRT) and enhance biogas production. The volatile and total solids, chemical oxygen demand (COD), alkalinity, and biogas composition were measured over one year. The proposed system achieved 87.40% COD remotion from the feed stream and generated a yield of 507 mLCH4 gVS −1, with an HRT of 19 days and an OLR of 4.27 gCOD L−1 d −1. The reactor produced biogas with a CH4 content of 67.7%, CO2 content of 18.1%, and H2S content of 1413 ppm. This study highlights the effectiveness of the UASB reactor for biogas production using swine manure as a substrate.